Direct-Write Deposition of Thermogels - Giannitelli, Sara Maria; Chiono, Valeria; Mozetic, Pamela (Methods in molecular biology, 2021)
The use of biocompatible hydrogels has widely extended the potential of additive manufacturing (AM) in the biomedical field leading to the production of 3D tissue and organ analogs for in vitro and in vivo studies.In this work, the direct-write deposition of thermosensitive hydrogels is described as a facile route to obtain 3D cell-laden constructs with controlled 3D structure and stable behavior under physiological conditions.
Keywords: hydrogely; polymery; Hydrogels; Printing, Three-Dimensional; Alginates; tkáňové inženýrství; Polymers; Tissue Engineering; lidé; Tissue Scaffolds; mikrotechnologie; Poloxamer; poloxamer; 3D tisk; Humans; Microtechnology; algináty; tkáňové podpůrné struktury